Investigating Systemic Immunity to Typhoid and Paratyphoid Fever: Characterising the Response to Re-challenge in a Controlled Human Infection Model. (4th October 2017) - M Gibani, Malick; Jin, Celina; Thomaides-Brears, Helena; Shrestha, Sonu; Precaido-Llanes, Lorena; Napolitani, Giorgio; Simmons, Alison; Gordon, Melita; Angus, Brian; Cerundolo, Vincenzo; Pollard, Andrew J
Abstract: Background: Infection with Salmonella Typhi is thought to confer partial, but incomplete, immunity against subsequent attacks of enteric fever. Empirical data underlying this hypothesis are limited and there are few studies describing underlying immunological correlates of protection, the extent of immunity conferred by Salmonella Paratyphi infection and the occurrence of heterologous-protection between these closely related serovars. Methods: Using an established controlled human infection model (CHIM) we recruited healthy volunteers into two groups: (1) Naive volunteers with no prior exposure to Salmonella Typhi/Paratyphi; and (2) volunteers previously-exposed to Salmonella Typhi / Paratyphi in earlier challenge studies. Participants were randomised 1:1 to oral-challenge with either Salmonella Typhi (10 4 CFU) or Paratyphi A (10 3 CFU). The primary objective was to compare the attack-rate after challenge between naive and previously-challenged individuals. Results: The attack-rate in participants who underwent homologous re-challenge with Salmonella Typhi ( n = 18) was 50% (95% CI 26-74%) compared with 67% (38-88%) in naive controls ( n = 15) and 65% (41–84%; n = 20) in previous naive-subject CHIM (Fig 1). Homologous re-challenge with Salmonella Paratyphi ( n = 13) resulted in an attack-rate of 23%(8-50%) compared with 67% (38-88%) in naive controls ( n = 15) and 60% (36-81%; n = 20) in previous naive-subject CHIM (Fig 2 ). Baseline anti-O:2 IgG was higher in paratyphoid re-challenge participants compared with naive controls. The attack-rate differed amongst participants who underwent heterologous re-challenge with Salmonella Typhi (70%; 40–89%; n = 10) or Salmonella Paratyphi (53%; 28-77%; n = 17) (Fig 1 and 2 ). Conclusion: These are the first data from human-challenge studies that indicate prior Salmonella Paratyphi exposure confers protection against re-challenge using a homologous strain in a non-endemic setting, suggesting that live-oral vaccines could be tested using this model. Prior Salmonella Typhi exposure conferred modest protection against homologous re-challenge, comparable to that observed in historical studies. Characterisation of correlates of protection identified using a challenge-rechallenge model could facilitate the development of novel vaccines for typhoidal Salmonella. Disclosures: A. J. Pollard, Pfizer/GSK/Astra Zeneca: Departmental educational grant in July 2016 for a course on Infection and Immunity in Children, Educational grant